Pengaruh Kepuasan dan Motivasi Kerja Karyawan terhadap Etos Kerja serta Implikasinya terhadap Kinerja Karyawan Pelaksana Pada Kebun dan Pabrik Kelapa Sawit PTPN III - Cahyadi, Yudhi; Lubis, Yusniar; Lubis, Syaifuddin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2021)
This study aims to determine the effect of employee satisfaction and work motivation on work ethic and its implications for the performance of implementing employees at the oil palm plantations and mills of PT. Perkebunan Nusantara III. Subjects in this study were employees of PTPN III. The research objects were employee satisfaction, work motivation, work ethic and performance of PTPN III employees. The sample in this study were 310 employees. Data analysis uses path analysis which aims to determine the causal relationship, with the aim of explaining the direct effect and indirect effect of a set of variables, as a causal variable on other variables which are effect variables. The results showed that employee satisfaction had a positive and significant effect on the work ethic of the implementing employees by 15,1%. Work motivation has a positive and significant effect on the work ethic of the implementing employees by 74,8%. The effect of Job Satisfaction (X1) and Work Motivation (X2) on Work Ethics (Y) is 50,1%. Employee Satisfaction has a positive and significant effect on the Performance of Implementing Employees by 6,7%. Work motivation has a positive and significant effect on the Performance of Implementing Employees by 20,8%. Work Ethic has a positive and significant effect on Employee Performance 76,7%. The influence of employee satisfaction, work motivation and work ethic on employee performance is 80.9%. The value of the direct effect of the employee satisfaction variable (x1) on the employee performance variable (z) is smaller than the influence of the employee satisfaction variable (x1) on the employee performance (z) through the work ethic (y), so it can be concluded that the work ethic variable (y) plays a role. as a full mediator because through the y variable, the x1 variable is able to significantly influence the z variable.